PERSEPSI MITRA BINAAN TERHADAP PROGRAM PEMBERDAYAAN UMKM TAMAN PURI AYU OLEH PT PLN INDONESIA POWER UBP JERANJANG DI DESA TAMAN AYU KABUPATEN LOMBOK BARAT - Fatmawati, Bella; Hadi, Agus Purbathin; Riyayanatasya, Yy Wima; Dwiputri, Tristiayu Permata; Soaedy, Febbri Herning (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
This study aims to determine the perception of fostered partners on the Taman Puri Ayu MSME empowerment program by PT PLN Indonesia Power UBP Jeranjang in Taman Ayu Village, West Lombok Regency. The method used in this research is descriptive qualitative. The data collection techniques used were observation, in-depth interviews, and documentation. Determination of informants in this study used purposive sampling technique, and involved four main informants and two supporting informants. The data analysis technique formulated is Miles and Huberman's with the stages of data reduction, data presentation, and conclusion drawing/verification. The results of this study indicate that the Taman Puri Ayu MSME empowerment program by PT PLN Indonesia Power UBP Jeranjang has several positive impacts, including increased business management skills, product packaging and marketing, which are obtained through training, mentoring, and coaching provided by PT PLN Indonesia Power UBP Jeranjang. Thus making the fostered partners feel more confident in developing their business, especially in expanding the local product market. In addition, the support facilities provided also help increase production capacity, although there are obstacles in communication and fulfillment of production equipment needs, which are still challenges that need to be improved. Overall, the program is considered beneficial, but still requires improvement in certain aspects